Assessment of retinal and choroidal microcirculatory alterations following radiofrequency catheter ablation in atrial fibrillation patients using swept-source optical coherence tomography angiography - Jin Wang; Huiran Yang; Qingjian Li; Yucen Wang; Pei Zhang; Pei Zhang; Zhiliang Wang (Frontiers in Cell and Developmental Biology)
PurposeThis study employed swept-source optical coherence tomography angiography (SS-OCTA) to explore potential hemodynamic alterations in the retina and choroid following radiofrequency catheter ablation (RFCA) for atrial fibrillation (AF).MethodsA total of 58 eyes from 32 patients were included, with SS-OCTA examinations conducted preoperatively and 1 day postoperatively. The evaluated parameters encompassed vessel density (VD) of the superficial vascular complex (SVC), VD of the deep vascular complex (DVC), choroidal vascular index (CVI), choroidal thickness (CT), thickness of the superficial retinal layer (SRL), and thickness of the deeper retinal layer (DRL).ResultsResults indicated no significant changes in the VD of the SVC and DVC, nor in the thickness of the superficial and deeper retinal layers. Conversely, CT demonstrated a significant increase (P < 0.05) and the CVI exhibited a notable rise exclusively within the 1-mm diameter region centered on the fovea (P < 0.05).ConclusionThese findings underscore the remarkable hemodynamic stability of retinal microcirculation in the early postoperative phase. The observed increase in CT and localized elevation in CVI may signify compensatory mechanisms involving enhanced postoperative choroidal perfusion and redistribution of cardiac output, thereby reinforcing the choroid’s superior sensitivity as a biomarker for detecting subtle hemodynamic shifts in AF-related ocular pathology.